Advanced Microsystems for Automotive Applications 2018 Smart Systems for Clean, Safe and Shared Road Vehicles - Dubbert, Jörg.; Müller, Beate; Meyer, Gereon; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This volume of the Lecture Notes in Mobility series contains papers written by speakers at the 22nd International Forum on Advanced Microsystems for Automotive Applications (AMAA 2018) "Smart Systems for Clean, Safe and Shared Road Vehicles" that was held in Berlin, Germany in September 2018. The authors report about recent breakthroughs in electric and electronic components and systems, driver assistance, vehicle automation and electrification as well as data, clouds and machine learning. Furthermore, innovation aspects and impacts of connected and automated driving are covered. The target audience primarily comprises research experts and practitioners in industry and academia, but the book may also be beneficial for graduate students alike. .
Smart Sensors -- Driver Assistance & Vehicle Automation -- Data, Clouds & Machine Learning -- Electric Vehicles -- Innovation Strategy.
Keywords: Automotive engineering; Transportation engineering; Traffic engineering; Microtechnology; Microelectromechanical systems; Sustainability; Electronic circuits; Automotive Engineering; Transportation Technology and Traffic Engineering; Microsystems and MEMS; Sustainability; Electronic Circuits and Systems